National housing policy (Lagos : Federal Ministry of Housing and Environment, 1980)
It is important that in a developing country like Nigeria, housing as one of the major claimants to the available resources, must require comprehensive and explicit guidelines in the form of a national housing policy if the housing problem is to be resolved in a way compatible with the demands of all other sectors.
ahz 04/04/2019
Ref.
Keywords: Economic development; Housing policy; Nigeria